Pengabdian Kepada Masyarakat Pelatihan Pembuatan Pakan Pellet Moist Untuk Budidaya Lobster Di Dusun Ujung Betok, Pemongkong Jerowaru, Lombok Timur - Alim, Sahrul; Yuliana Asri; Wastu Ayu Diamahesa; Septiana Dwiyanti; Nuri Muahiddah; Damai Diniariwisan; Muhammad Sumsanto; Rangga Idris Affandi; Bagus Dwi Hari Setyono; Thoy Batun Citra Rahmadani (Universitas Mataram, 2024)
Community service is an activity with the aim of providing skills-based literacy to community groups, in this case the lobster cultivating community in Ujung Betok Village, Pemongkong Jerowaru, East Lombok. The methods used during training are interactive discussions and work practices. This training activity was attended by lecturers from the Aquaculture Study Program as training resource persons, students and groups of lobster farmers. The activity took place at the residence of the group leader as a gathering and discussion forum for lobster cultivators in Ujung Betok Village. This activity was carried out as an effort to reduce dependence on trash fish feed, the availability of which fluctuates greatly according to the fishing season. Apart from that, this training is expected to be able to increase the efficiency of lobster cultivation. This training includes material on proper nutritional composition, ingredient mixing techniques, processing processes, and good feeding methods. The results of this training show an increase in the participants' ability to produce quality feed which is expected to have a positive impact on the growth and health of the lobsters being farmed. Apart from that, this initiative is also expected to contribute to improving the welfare of local communities through the development of more sustainable and efficient lobster cultivation. Keyword : Pakan, moist, lobster